CEUS/CT fusion navigation for detection and interventional drainage of hidden peripancreatic abscesses in acute pancreatitis: a case report - Wu, Yuquan; Gao, Ruizhi; Pang, Jinshu; He, Yun; Yang, Hong (Frontiers in Medicine, 2025)
Background and aimsMultimodal imaging virtual fusion navigation offers higher accuracy and real-time guidance compared to single imaging modalities. This case report explores the value of contrast-enhanced ultrasound (CEUS)/CT fusion navigation in the localization, characterization, and interventional guidance of a hidden peripancreatic abscess in acute pancreatitis.MethodsThe case involved the use of contrast-enhanced ultrasound and CT virtual fusion navigation to identify and assess the hidden peripancreatic abscess in a patient diagnosed with acute pancreatitis. The fusion technology allowed for real-time navigation during interventional procedures, offering improved lesion localization and characterization.ResultsCEUS/CT fusion navigation successfully localized and characterized the hidden peripancreatic abscess. The real-time navigation provided by the fusion technology improved the accuracy and safety of the interventional procedure.ConclusionCEUS/CT fusion navigation technology demonstrated significant value in the precise localization, detailed characterization, and effective interventional guidance of a hidden peripancreatic abscess in acute pancreatitis. This approach offers a promising tool for managing similar complex cases in clinical practice.